Oxide synergized glass fiber reinforced phenolic molding compound and method of making same
Patent Information
- Application Number
- CN202611363738.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-09-04
AI Technical Summary
[0006]针对现有技术中酚醛模塑料存在的脆性大、韧性差、绝缘强度差、耐热性差等问题,本发明提供一种氧化物协同玻璃纤维增强酚醛模塑料及其制备方法
[0046](1)本发明提供的氧化物协同玻璃纤维增强酚醛模塑料及其制备方法,在氧化铝表面共同化学锚定含硼有机物和硅烷偶联剂,并将修饰后的氧化铝引入酚醛树脂合成体系,纳米氧化铝提供增韧作用,硼元素通过高键能B-O键提升树脂的耐热性,硅元素通过Al-O-Si-树脂网络结构增强材料的耐水解性和电绝缘性能,三者协同作用,使所制备的酚醛树脂韧性增强、耐热提升和绝缘性能提升,综合改善酚醛模塑料性能。
Smart Images

Figure CN122854734B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of special phenolic resin technology, and discloses an oxide-synergistic glass fiber reinforced phenolic molding compound and its preparation method. Background Technology
[0002] Phenolic molding compounds are thermosetting plastics made by using phenolic resin as a binder, adding reinforcing fibers, fillers, and additives through mixing, plasticizing, and pulverizing. Due to their excellent mechanical strength, good electrical insulation, chemical resistance, and low cost, they are widely used in electrical and electronic, automotive parts, and machinery manufacturing industries. With the increasing demands on material performance from new energy vehicles and high-end equipment manufacturing, the market demand for phenolic molding compounds that combine higher heat resistance, mechanical strength, and processing performance is becoming increasingly urgent.
[0003] While traditional phenolic molding compounds improve the mechanical strength of the matrix by introducing glass fibers, phenolic resin is brittle and lacks toughness. The introduction of glass fibers does not effectively improve the toughness of phenolic molding compounds, and they are prone to thermal degradation at high temperatures. To improve heat resistance and toughness, the industry often tries to add inorganic fillers such as alumina. However, alumina particles are rich in hydroxyl groups on their surface, making them highly polar. They have poor compatibility with non-polar or weakly polar organic resin matrices and are prone to agglomeration. This agglomeration not only leads to uneven distribution of fillers in the matrix, forming stress concentration points and severely weakening the material's mechanical properties, but also causes microcracks due to poor interfacial bonding, reducing the material's electrical insulation strength and resistance to damp heat.
[0004] To address the alumina dispersion problem, existing technologies often employ simple physical mixing or surface treatment with conventional silane coupling agents. While silane coupling agents can improve interfacial bonding to some extent, single-silicon modification often fails to simultaneously meet the multiple requirements of high heat resistance, high insulation, and high toughness. Furthermore, the conventional method of adding fillers after resin synthesis struggles to achieve deep integration between the filler and resin molecules, resulting in limited interfacial bonding. In recent years, although some studies have attempted to introduce nanomaterials or modify resins, such as epoxy modification and polyvinyl butyral modification, these methods are either complex and costly, or they sacrifice other properties while improving one, making it difficult to meet the extreme requirements of comprehensive material performance for new energy vehicles and high-end electrical components.
[0005] Therefore, developing an oxide-synergistic glass fiber reinforced phenolic molding compound and its preparation method is of great practical significance and application value for breaking through the current technical bottleneck of high-performance composite materials and meeting the material needs of key components in the automotive and new energy fields. Summary of the Invention
[0006] To address the problems of high brittleness, poor toughness, poor insulation strength, and poor heat resistance in existing phenolic molding compounds, this invention provides an oxide-synergistic glass fiber reinforced phenolic molding compound and its preparation method.
[0007] To achieve the above objectives, this application adopts the following technical solution:
[0008] In one aspect, the present invention provides an oxide-synergistic glass fiber reinforced phenolic molding compound, comprising modified phenolic resin, glass fiber, filler, and release agent;
[0009] The modified phenolic resin is prepared by the following steps:
[0010] (1) Boron-containing organic compounds modified with isocyanate were prepared by reacting p-phenylenediisocyanate and pinacol ester of 2-hydroxyphenylboronic acid;
[0011] (2) Surface-modified nano-Al2O3 was prepared by reacting isocyanate-modified boron-containing organic compounds, silane coupling agents and nano-Al2O3.
[0012] (3) The modified phenolic resin was prepared by reacting phenol, formaldehyde aqueous solution and surface-modified nano-Al2O3.
[0013] Preferably, the specific method of step (1) is as follows: under nitrogen protection, terephthalic diisocyanate and organic solvent are added to the reaction vessel, mixed evenly, and then 2-hydroxyphenylboronic acid pinacol ester is added. After reacting at 22-26℃ for 15-18 hours, the isocyanate-modified boron-containing organic compound is purified.
[0014] The isocyanate-modified boron-containing organic compound has the structure shown in Formula A:
[0015] .
[0016] Preferably, the molar ratio of terephthalic diisocyanate to pinacol 2-hydroxyphenylboronic acid is (1.1-1.3):1;
[0017] The organic solvent is selected from one of dichloroethane, ethyl acetate, toluene, or chloroform.
[0018] Preferably, the specific method of step (2) is as follows: disperse nano-Al2O3 in an aqueous ethanol solution, add silane coupling agent, adjust pH to 3-5, stir and react at 20-25℃ for 1-2 hours, centrifuge, wash and dry to obtain modified nano-Al2O3, then disperse the modified nano-Al2O3 in anhydrous toluene, add isocyanate to modify boron-containing organic matter, react at 60-80℃ for 4-6 hours, centrifuge, wash and dry to obtain surface-modified nano-Al2O3.
[0019] Preferably, the average particle size of the nano-Al2O3 is 20-100 nm;
[0020] The silane coupling agent is selected from either KH-560 or KH-570;
[0021] The mass ratio of the isocyanate-modified boron-containing organic compound, the silane coupling agent, and the nano-Al2O3 is (1.5-5):(1.5-5):100;
[0022] The volume concentration of the ethanol aqueous solution is 5-15%.
[0023] In this invention, after the nano-Al2O3 is modified with a small amount of silane coupling agent, a large number of hydroxyl groups are still retained on the surface of the nano-alumina, which can be further modified. Subsequently, by adding an excess of nano-Al2O3, all the isocyanate groups of the boron-containing organic matter are reacted by the isocyanate modification.
[0024] The surface of nano-Al2O3 contains a large number of active hydroxyl groups. The isocyanate-modified boron-containing organic compound has an active isocyanate group (-NCO) at one end and a boron ester structure containing pinacol ester at the other end. The carbon atom in the -NCO group is strongly positively charged because it is connected to the highly electronegative nitrogen and oxygen. The hydroxyl group on the Al2O3 surface acts as a nucleophile, attacking the carbon atom in the -NCO group and undergoing nucleophilic addition to generate a carbamate bond (-NHCOO-). This chemically bonds the entire boron-containing molecular structure to the Al2O3 surface, thus introducing boron into the Al2O3 surface.
[0025] In the presence of water, the alkoxy group in the silane coupling agent molecule hydrolyzes to generate an active silanol group. The silanol group undergoes a dehydration condensation reaction with the hydroxyl group on the Al2O3 surface to form a Si-O-Al covalent bond, which fixes the silane molecule on the alumina surface. Silicon and organic functional groups are introduced into the alumina surface.
[0026] The two modifiers are anchored on the Al2O3 surface through -NHCOO- bonds and Si-O-Al bonds, respectively, forming a composite organic layer on the nanoparticle surface that has both boron-containing and silicon-containing structures. This not only improves the dispersibility of Al2O3, but also reserves chemical sites for subsequent reactions with phenolic resin.
[0027] Preferably, the specific method of step (3) is as follows: phenol, formaldehyde aqueous solution and alkaline catalyst are added to the reaction vessel, reacted at 60-95℃ for 1-2 hours, surface-modified nano Al2O3 is added, reacted for 2-4 hours, and then dehydrated to obtain the modified phenolic resin.
[0028] Preferably, the alkaline catalyst is selected from sodium hydroxide or potassium hydroxide;
[0029] The mass concentration of the formaldehyde aqueous solution is 30-40%;
[0030] The molar ratio of phenol, formaldehyde, and alkaline catalyst is 1:(1.4-1.6):(0.05-0.1).
[0031] The amount of surface-modified nano-Al2O3 added is 1-5% of the mass of phenol.
[0032] Isocyanate-modified boron-containing organic compounds decompose into active phenylboronic acid structures and pinacol under alkaline conditions. The boron hydroxyl groups in the phenylboronic acid structure undergo dehydration condensation with the phenolic hydroxyl groups of the phenolic resin to form BOC bonds, grafting boron elements into the phenolic resin chain segments. The bond energy of the BO bond is much higher than that of the C-C bond, forming a B2O3 protective layer at high temperatures, which significantly improves the resin's carbon residue and thermal stability. Meanwhile, pinacol, with its high boiling point, remains in the resin network, increasing the free volume between molecular chains and enhancing its flexibility and processability.
[0033] After the silane coupling agent is fixed on the surface of Al2O3 through Si-O-Al bonds, the epoxy group of KH-560 can react with the phenolic hydroxyl group during the synthesis of phenolic resin to form a chemical bond of Al2O3-Si-phenolic resin, while the methacryloyloxy group of KH-570 can improve the compatibility between the modified layer and the resin matrix, thereby enhancing the hydrolysis resistance and electrical insulation properties of the material.
[0034] This invention utilizes the chemical bonding and dispersion of nano-Al2O3, the introduction of boron into the resin network in the form of BOC bonds, and the Al-O-Si-resin network of silicon to synergistically enhance the rigidity, improve the heat resistance, and toughen the interface of the prepared phenolic resin, thereby comprehensively improving the performance of molding compounds.
[0035] Preferably, the glass fiber is a short-cut glass fiber with a length of 3-6 mm;
[0036] The packing material is composed of organic packing material and inorganic packing material;
[0037] The organic filler is selected from at least one of wood flour or bamboo flour;
[0038] The inorganic filler is selected from at least one of mica powder, CaCO3, talc powder, quartz powder or kaolin.
[0039] The mass ratio of the organic filler to the inorganic filler is (1-1.2):(1-1.2).
[0040] The release agent is selected from one of zinc stearate, calcium stearate, or stearic acid.
[0041] Preferably, by weight, it comprises the following components: 90-110 parts modified phenolic resin, 30-60 parts glass fiber, 20-60 parts filler, and 1-3 parts release agent.
[0042] Another aspect of the present invention provides a method for preparing any one of the above-mentioned oxide-synergistic glass fiber reinforced phenolic molding compounds, comprising the following steps:
[0043] (1) Mix the modified phenolic resin, glass fiber, filler and release agent at 20-30℃ for 8-20 minutes in proportion to obtain a powder;
[0044] (2) Then the powdered material is mixed at 90-130℃ for 3-15 minutes, cooled and crushed to obtain the oxide-co-glass fiber reinforced phenolic molding compound.
[0045] The technical effects and advantages of this invention are as follows:
[0046] (1) The oxide-co-glass fiber reinforced phenolic molding compound and its preparation method provided by the present invention chemically anchor boron-containing organic matter and silane coupling agent on the surface of alumina, and introduce the modified alumina into the phenolic resin synthesis system. Nano-alumina provides toughening effect, boron element improves the heat resistance of resin through high bond energy BO bond, and silicon element enhances the hydrolysis resistance and electrical insulation performance of material through Al-O-Si-resin network structure. The three work together to enhance the toughness, heat resistance and insulation performance of the prepared phenolic resin, and comprehensively improve the performance of phenolic molding compound.
[0047] (2) In the oxide-co-glass fiber reinforced phenolic molding compound provided by the present invention, nano-alumina acts as a physical cross-linking point in the resin matrix, absorbing and dispersing impact energy, thereby improving the toughness of the material; at the same time, the addition of nano-alumina can also reduce the curing temperature of phenolic resin, which is conducive to energy saving, consumption reduction and production efficiency improvement.
[0048] (3) In the oxide-co-glass fiber reinforced phenolic molding compound provided by the present invention, the free isocyanate groups in the boron-containing organic matter modified by isocyanate chemically bond with the hydroxyl groups on the surface of alumina, thereby reducing the surface energy of alumina and preventing secondary agglomeration during the mixing process, thus achieving uniform dispersion of alumina in the phenolic resin matrix; at the same time, a silane coupling agent is introduced, which forms covalent bonds with the hydroxyl groups on the surface of alumina, further improving its dispersibility; through the synergistic effect of isocyanate and silane coupling agent, the problem of easy agglomeration and uneven dispersion of alumina in the resin matrix is solved.
[0049] (4) In the oxide-co-glass fiber reinforced phenolic molding compound provided by the present invention, when alumina with isocyanate-modified boron-containing organic matter is added to the synthesis process of phenolic resin, the isocyanate-modified boron-containing organic matter decomposes into active phenylboronic acid structure and pinacol under alkaline conditions. The boron hydroxyl group in the phenylboronic acid structure undergoes dehydration condensation with the phenolic hydroxyl group of phenolic resin to form BOC bond. By grafting boron element into the phenolic resin chain segment, a B2O3 protective layer can be formed at high temperature, which significantly improves the carbon residue rate and thermal stability of the resin. Meanwhile, pinacol remains in the resin network, increasing the free volume between molecular chains, thereby increasing its flexibility and processability.
[0050] (5) In the oxide-co-glass fiber reinforced phenolic molding compound provided by the present invention, after the silane coupling agent is fixed on the surface of Al2O3 through Si-O-Al bond, in addition to improving the dispersibility of alumina, the epoxy group of KH-560 can react with the phenolic hydroxyl group during the phenolic synthesis process to form a chemical bond of Al2O3-Si-phenolic resin, while the methacryloyloxy group of KH-570 can improve the compatibility between the modified layer and the resin matrix, thereby enhancing the hydrolysis resistance and electrical insulation properties of the material.
[0051] (6) The oxide-co-glass fiber reinforced phenolic molding compound provided by the present invention has excellent toughness, thermal stability, electrical insulation and hydrolysis resistance, as well as good processing fluidity and flame retardant properties. It can be widely used in the field of high-performance glass fiber composite materials such as automobile start switches, thermostats, brake system accessories, DC motor commutators, motor brush holders, high-end transformer coil frames and new energy vehicle batteries and charging piles. Attached Figure Description
[0052] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention.
[0053] Figure 1 This is a flowchart illustrating the preparation process of the oxide-coated glass fiber reinforced phenolic molding compound of the present invention.
[0054] Figure 2 The infrared spectrum of the isocyanate-modified boron-containing organic compound of this invention;
[0055] Figure 3 This is the infrared spectrum of the modified phenolic resin of this invention. Detailed Implementation
[0056] It is readily understood that, based on the technical solutions of this invention, those skilled in the art can propose various interchangeable structural methods and implementations without departing from the spirit or scope of this invention. Therefore, the following detailed embodiments and accompanying drawings are merely illustrative examples of the technical solutions of this invention and should not be considered as the entirety of this invention or as limitations or restrictions on the technical solutions of this invention.
[0057] In this invention, the CAS number of terephthalic diisocyanate is 104-49-4; the CAS number of pinacol ester of 2-hydroxyphenylboronic acid is 269409-97-4; silane coupling agents KH-560 and KH-570 were purchased from Shanghai Mairui; nano Al2O3 was purchased from Shanghai Jinchuang Chemical; and the remaining reagents, glass fibers, fillers, and release agents are conventional reagents in this technical field.
[0058] Example 1
[0059] Preparation of modified phenolic resin:
[0060] (1) The raw materials were weighed according to the molar ratio of terephthalic diisocyanate to pinacol 2-hydroxyphenylboronic acid ester of 1.2:1. Under nitrogen protection, terephthalic diisocyanate and dichloroethane were added to the reaction vessel and mixed evenly. Then, pinacol 2-hydroxyphenylboronic acid ester was added. After reacting at 24°C for 16 hours, the crude product was obtained by suction filtration. The crude product was washed three times with ethyl acetate. The filter cake was filtered until dry. The crude product was transferred to a round-bottom flask, ethyl acetate was added, and the mixture was heated to reflux until completely dissolved. The mixture was filtered while hot. The filtrate was naturally cooled to 23°C and then placed at 2°C for crystallization for 12 hours. After suction filtration and washing, the mixture was dried at 50°C to constant weight to obtain the purified isocyanate-modified boron-containing organic compound. The infrared spectrum of the isocyanate-modified boron-containing organic compound is shown below. Figure 2 As shown;
[0061] (2) Weigh isocyanate-modified boron-containing organic matter, silane coupling agent KH-560 and nano-Al2O3 with an average particle size of 50 nm in a mass ratio of 3.2:3.2:100. Disperse the nano-Al2O3 in a 10% ethanol aqueous solution, add silane coupling agent KH-560, add glacial acetic acid to adjust the pH to 4, stir and react at 23°C for 1.5 hours, centrifuge, wash and dry to obtain modified nano-Al2O3, then disperse the modified nano-Al2O3 in anhydrous toluene, add isocyanate-modified boron-containing organic matter, react at 70°C for 5 hours, centrifuge, wash and dry to obtain surface-modified nano-Al2O3;
[0062] (3) Phenol, formaldehyde, and sodium hydroxide were weighed in a molar ratio of 1:1.5:0.08, and a 35% (w / w) aqueous solution of formaldehyde was prepared. All three were added to a reaction vessel and reacted at 80°C for 1.5 hours. Surface-modified nano-Al2O3 was then added, with the amount of surface-modified nano-Al2O3 being 3% of the mass of phenol. After reacting for 3 hours, the mixture was dehydrated to obtain the modified phenolic resin. The infrared spectrum of the modified phenolic resin is shown below. Figure 3 As shown.
[0063] Preparation of oxide-coated glass fiber reinforced phenolic molding compound:
[0064] Based on the mass fractions, take 100 parts of modified phenolic resin, 45 parts of short glass fiber with a length of 4 mm, 40 parts of filler, and 2 parts of zinc stearate as a release agent. The filler is composed of wood flour and mica powder in a mass ratio of 1:1.
[0065] (1) The modified phenolic resin, chopped glass fiber, filler and release agent are mixed at 25°C for 15 minutes to obtain a powder.
[0066] (2) Then the powdered material is mixed at 110°C for 10 minutes, cooled and crushed to obtain the oxide-co-glass fiber reinforced phenolic molding compound.
[0067] Example 2
[0068] Preparation of modified phenolic resin:
[0069] (1) Weigh the raw materials according to the molar ratio of terephthalic diisocyanate to pinacol 2-hydroxyphenylboronic acid in the ratio of 1.1:1. Under nitrogen protection, add terephthalic diisocyanate and ethyl acetate to the reaction vessel, mix evenly, add pinacol 2-hydroxyphenylboronic acid, react at 22°C for 15 hours, filter to obtain crude product, wash with ethyl acetate 3 times, filter the filter cake to dry state, transfer the crude product to a round bottom flask, add ethyl acetate, heat to reflux to completely dissolve, filter while hot, cool the filtrate naturally to 20°C, place it at 0°C to crystallize for 10 hours, filter and wash, dry at 45°C to constant weight, and obtain purified isocyanate modified boron-containing organic compound;
[0070] (2) Weigh isocyanate-modified boron-containing organic matter, silane coupling agent KH-570 and nano-Al2O3 with an average particle size of 20 nm in a mass ratio of 1.5:1.5:100. Disperse the nano-Al2O3 in an ethanol aqueous solution with a volume concentration of 5%, add silane coupling agent KH-570, add glacial acetic acid to adjust the pH to 3, stir and react at 20°C for 1 hour, centrifuge, wash and dry to obtain modified nano-Al2O3, then disperse the modified nano-Al2O3 in anhydrous toluene, add isocyanate-modified boron-containing organic matter, react at 60°C for 4 hours, centrifuge, wash and dry to obtain surface-modified nano-Al2O3;
[0071] (3) Phenol, formaldehyde and sodium hydroxide were weighed in a molar ratio of 1:1.4:0.05, and the formaldehyde was prepared into a 30% formaldehyde aqueous solution. The three were added to the reaction vessel and reacted at 60°C for 1 hour. Then, surface-modified nano-Al2O3 was added. The amount of surface-modified nano-Al2O3 added was 1% of the mass of phenol. After reacting for 2 hours, the modified phenolic resin was obtained by dehydration.
[0072] Preparation of oxide-coated glass fiber reinforced phenolic molding compound:
[0073] Based on mass parts, take 94 parts of modified phenolic resin, 32 parts of short glass fiber with a length of 3 mm, 60 parts of filler and 1 part of calcium stearate as release agent. The filler is composed of bamboo powder and talc powder in a mass ratio of 1:1.2.
[0074] (1) The modified phenolic resin, chopped glass fiber, filler and release agent were mixed at 20°C for 8 minutes to obtain a powder.
[0075] (2) Then the powdered material is mixed at 90°C for 3 minutes, cooled and crushed to obtain the oxide-co-glass fiber reinforced phenolic molding compound.
[0076] Example 3
[0077] Preparation of modified phenolic resin:
[0078] (1) Weigh the raw materials according to the molar ratio of terephthalic diisocyanate to pinacol 2-hydroxyphenylboronic acid in the ratio of 1.3:1. Under nitrogen protection, add terephthalic diisocyanate and toluene to the reaction vessel, mix evenly, add pinacol 2-hydroxyphenylboronic acid, react at 26°C for 18 hours, filter to obtain crude product, wash with ethyl acetate 3 times, filter the filter cake to dry state, transfer the crude product to a round bottom flask, add ethyl acetate, heat to reflux to completely dissolve, filter while hot, cool the filtrate to 25°C naturally, place it at 4°C to stand for crystallization for 14 hours, filter and wash, dry at 55°C to constant weight, and obtain purified isocyanate modified boron-containing organic compound;
[0079] (2) Weigh isocyanate-modified boron-containing organic matter, silane coupling agent KH-560 and nano-Al2O3 with an average particle size of 100 nm in a mass ratio of 5:5:100. Disperse the nano-Al2O3 in an ethanol aqueous solution with a volume concentration of 15%, add silane coupling agent KH-560, add glacial acetic acid to adjust the pH to 5, stir and react at 25°C for 2 hours, centrifuge, wash and dry to obtain modified nano-Al2O3, then disperse the modified nano-Al2O3 in anhydrous toluene, add isocyanate-modified boron-containing organic matter, react at 80°C for 6 hours, centrifuge, wash and dry to obtain surface-modified nano-Al2O3;
[0080] (3) Phenol, formaldehyde and sodium hydroxide were weighed in a molar ratio of 1:1.6:0.1, and the formaldehyde was prepared into a 40% formaldehyde aqueous solution. The three were added to the reaction vessel and reacted at 95°C for 2 hours. Then, surface-modified nano-Al2O3 was added. The amount of surface-modified nano-Al2O3 added was 5% of the mass of phenol. After reacting for 4 hours, the modified phenolic resin was obtained by dehydration.
[0081] Preparation of oxide-coated glass fiber reinforced phenolic molding compound:
[0082] Based on mass parts, take 110 parts of modified phenolic resin, 54 parts of short glass fiber with a length of 6 mm, 20 parts of filler and 3 parts of release agent stearic acid. The filler is composed of wood flour and CaCO3 in a mass ratio of 1.2:1.
[0083] (1) The modified phenolic resin, chopped glass fiber, filler and release agent are mixed at 30°C for 20 minutes to obtain a powder;
[0084] (2) The powdered material is then mixed at 130°C for 15 minutes, cooled, and pulverized to obtain the oxide-co-glass fiber reinforced phenolic molding compound.
[0085] Comparative Example 1
[0086] The process is basically the same as in Example 1. The difference between Example 1 and Example 1 is that in step (3) of the preparation of modified phenolic resin, the surface-modified nano-Al2O3 is replaced with an equal amount of phenol.
[0087] Comparative Example 2
[0088] The process is basically the same as in Example 1. The difference between Example 1 and Example 1 is that in step (3) of the preparation of modified phenolic resin, the surface-modified nano-Al2O3 is replaced with an equal amount of nano-Al2O3 with an average particle size of 50 nm.
[0089] Comparative Example 3
[0090] The process is basically the same as in Example 1. The difference between Example 1 and Example 1 is that step (2) of the preparation of modified phenolic resin is changed to: weighing silane coupling agent KH-560 and nano Al2O3 with an average particle size of 50 nm at a mass ratio of 6.4:100, dispersing nano Al2O3 in an ethanol aqueous solution with a volume concentration of 10%, adding silane coupling agent KH-560, adding glacial acetic acid to adjust the pH to 4, stirring and reacting at 23°C for 1.5 hours, centrifuging, washing, and drying to obtain modified nano Al2O3; in step (3) of the preparation of modified phenolic resin, the surface-modified nano Al2O3 is changed to an equal amount of modified nano Al2O3.
[0091] Comparative Example 4
[0092] The process is basically the same as in Example 1. The difference between Example 1 and Example 1 is that step (2) of the preparation of modified phenolic resin is changed to: weighing isocyanate-modified boron-containing organic matter and nano-Al2O3 with an average particle size of 50 nm at a mass ratio of 6.4:100, dispersing nano-Al2O3 in anhydrous toluene after drying at 120°C for 4 hours, adding isocyanate-modified boron-containing organic matter, reacting at 70°C for 5 hours, centrifuging, washing, and drying to obtain isocyanate-modified boron-containing organic matter-modified nano-Al2O3; in step (3) of the preparation of modified phenolic resin, the surface-modified nano-Al2O3 is changed to an equal amount of isocyanate-modified boron-containing organic matter-modified nano-Al2O3.
[0093] Performance testing
[0094] 1. Mechanical property testing
[0095] Test methods: The mechanical properties of the materials in Examples 1-3 and Comparative Examples 1-4 were tested according to the following standards. Tensile strength was tested according to GB / T 1040 standard, and flexural strength was tested according to GB / T 9341 standard. The maximum tensile and flexural strengths were recorded. Impact strength was tested according to GB / T 1043 standard, and the impact strength was recorded.
[0096] 2. Thermal decomposition temperature test
[0097] Test method: The thermal decomposition temperature was determined using a thermogravimetric analyzer. The samples were heated at a rate of 5 °C / min under a nitrogen atmosphere. The temperature at which the materials of Examples 1-3 and Comparative Examples 1-4 began to experience significant weight loss (5% mass loss) was recorded as the thermal decomposition temperature (Td).
[0098] The test results are shown in Table 1 below:
[0099] Table 1 Mechanical properties and thermal decomposition temperature
[0100]
[0101] 3. Heat distortion temperature test
[0102] Test method: According to GB / T 1634.2 standard, the temperature at which the materials of Examples 1-3 and Comparative Examples 1-4 underwent thermal deformation was recorded under the conditions of load 1.82MPa and heating rate 120℃ / h.
[0103] 4. Electrical insulation test
[0104] Test method: The volume resistivity of the materials in Examples 1-3 and Comparative Examples 1-4 was tested according to GB 1410 standard.
[0105] 5. Flame retardant performance test
[0106] Test method: The limiting oxygen index of the materials in Examples 1-3 and Comparative Examples 1-4 was tested according to GB / T 2406 standard.
[0107] 6. Processing fluidity test
[0108] Test method: The molding shrinkage rate of the materials in Examples 1-3 and Comparative Examples 1-4 was tested according to JB / T 6542 standard.
[0109] The test results are shown in Table 2 below:
[0110] Table 2. Tests for heat distortion temperature, electrical insulation, flame retardancy, and processing fluidity.
[0111]
[0112] A comparison of the test results of Example 1 and Comparative Example 1 shows that the present invention uses surface-modified nano-Al2O3 to replace phenol to synthesize modified phenolic resin, which is then mixed with glass fiber, filler and release agent to further prepare oxide-synergistic glass fiber reinforced phenolic molding compound. The mechanical properties are significantly improved, and the thermal stability, insulation, flame retardancy and dimensional stability are also improved. This indicates that using surface-modified nano-Al2O3 to replace phenol to synthesize modified phenolic resin has a significant beneficial effect on improving the mechanical properties, thermal stability, flame retardancy, insulation and processing fluidity of composite glass fiber materials.
[0113] A comparison of the test results of Example 1 and Comparative Example 2 shows that the present invention uses surface-modified nano-Al2O3 to replace nano-Al2O3 to synthesize modified phenolic resin, which is then mixed with glass fiber, filler and release agent to further prepare oxide-synergistic glass fiber reinforced phenolic molding compound. The mechanical properties are significantly improved, and the thermal stability, insulation, flame retardancy and dimensional stability are also improved. This indicates that using surface-modified nano-Al2O3 to replace nano-Al2O3 to synthesize modified phenolic resin has a significant beneficial effect on improving the mechanical properties, thermal stability, flame retardancy, insulation and processing fluidity of composite glass fiber materials.
[0114] A comparison of the test results of Example 1 and Comparative Example 3 shows that the present invention uses surface-modified nano-Al2O3 to replace silane coupling agent-modified nano-Al2O3 to synthesize modified phenolic resin, which is then mixed with glass fiber, filler, and release agent to further prepare oxide-synergistic glass fiber reinforced phenolic molding compound. The mechanical properties are significantly improved, and the thermal stability, insulation, and flame retardancy are also improved. This indicates that using surface-modified nano-Al2O3 to replace silane coupling agent-modified nano-Al2O3 to synthesize modified phenolic resin has a significant beneficial effect on improving the mechanical properties, thermal stability, flame retardancy, and insulation of composite glass fiber materials.
[0115] A comparison of the test results of Example 1 and Comparative Example 4 shows that the present invention uses surface-modified nano-Al2O3 to replace isocyanate-modified boron-containing organic-modified nano-Al2O3 to synthesize modified phenolic resin, which is then mixed with glass fiber, filler, and release agent to further prepare oxide-synergistic glass fiber reinforced phenolic molding compound. The mechanical properties are significantly improved, and the thermal stability and flame retardancy are also improved. This indicates that using surface-modified nano-Al2O3 to replace isocyanate-modified boron-containing organic-modified nano-Al2O3 to synthesize modified phenolic resin has a significant beneficial effect on improving the mechanical properties, thermal stability, and flame retardancy of composite glass fiber materials.
[0116] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. An oxide-synergistic glass fiber reinforced phenolic molding compound, characterized in that, Includes modified phenolic resin, glass fiber, filler, and release agent; The modified phenolic resin is prepared by the following steps: (1) Boron-containing organic compounds modified with isocyanate were prepared by reacting p-phenylenediisocyanate and pinacol ester of 2-hydroxyphenylboronic acid; (2) Surface-modified nano-Al2O3 was prepared by reacting isocyanate-modified boron-containing organic compounds, silane coupling agents and nano-Al2O3. (3) The modified phenolic resin was prepared by reacting phenol, formaldehyde aqueous solution and surface-modified nano-Al2O3.
2. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 1, characterized in that, The specific method of step (1) is as follows: under nitrogen protection, terephthalic diisocyanate and organic solvent are added to the reaction vessel, mixed evenly, and then 2-hydroxyphenylboronic acid pinacol ester is added. After reacting at 22-26℃ for 15-18 hours, the isocyanate-modified boron-containing organic compound is purified. The isocyanate-modified boron-containing organic compound has the structure shown in Formula A: 。 3. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 2, characterized in that, The molar ratio of terephthalic diisocyanate to pinacol 2-hydroxyphenylboronic acid is (1.1-1.3):1; The organic solvent is selected from one of dichloroethane, ethyl acetate, toluene, or chloroform.
4. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 1, characterized in that, The specific method of step (2) is as follows: Disperse nano-Al2O3 in an aqueous ethanol solution, add silane coupling agent, adjust pH to 3-5, stir and react at 20-25℃ for 1-2 hours, centrifuge, wash and dry to obtain modified nano-Al2O3, then disperse the modified nano-Al2O3 in anhydrous toluene, add isocyanate to modify boron-containing organic matter, react at 60-80℃ for 4-6 hours, centrifuge, wash and dry to obtain surface-modified nano-Al2O3.
5. The oxide-synergistic glass fiber reinforced phenolic molding compound according to claim 4, characterized in that, The average particle size of the nano-Al2O3 is 20-100 nm; The silane coupling agent is selected from either KH-560 or KH-570; The mass ratio of the isocyanate-modified boron-containing organic compound, the silane coupling agent, and the nano-Al2O3 is (1.5-5):(1.5-5):100; The volume concentration of the ethanol aqueous solution is 5-15%.
6. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 1, characterized in that, The specific method of step (3) is as follows: phenol, formaldehyde aqueous solution and alkaline catalyst are added to the reaction vessel, reacted at 60-95℃ for 1-2 hours, surface-modified nano Al2O3 is added, reacted for 2-4 hours, and then dehydrated to obtain the modified phenolic resin.
7. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 6, characterized in that, The alkaline catalyst is selected from sodium hydroxide or potassium hydroxide; The mass concentration of the formaldehyde aqueous solution is 30-40%; The molar ratio of phenol, formaldehyde, and alkaline catalyst is 1:(1.4-1.6):(0.05-0.1). The amount of surface-modified nano-Al2O3 added is 1-5% of the mass of phenol.
8. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 1, characterized in that, The glass fiber is a short-cut glass fiber with a length of 3-6 mm; The packing material is composed of organic packing material and inorganic packing material; The organic filler is selected from at least one of wood flour or bamboo flour; The inorganic filler is selected from at least one of mica powder, CaCO3, talc powder, quartz powder or kaolin. The mass ratio of the organic filler to the inorganic filler is (1-1.2):(1-1.2). The release agent is selected from one of zinc stearate, calcium stearate, or stearic acid.
9. The oxide-coated glass fiber reinforced phenolic molding compound according to claim 1, characterized in that, By weight, it includes the following components: 90-110 parts modified phenolic resin, 30-60 parts glass fiber, 20-60 parts filler, and 1-3 parts release agent.
10. The method for preparing the oxide-synergistic glass fiber reinforced phenolic molding compound according to any one of claims 1-9, characterized in that, Includes the following steps: (1) Mix the modified phenolic resin, glass fiber, filler and release agent at 20-30℃ for 8-20 minutes in proportion to obtain a powder; (2) Then the powdered material is mixed at 90-130℃ for 3-15 minutes, cooled and crushed to obtain the oxide-co-glass fiber reinforced phenolic molding compound.
Citation Information
Patent Citations
Preparation method of lignin and boron dual-modified phenolic resin and phenolic moulding plastic
CN105754058A
Modified phenolic resin and preparation method thereof
CN117264148A
